The Effect Of Brand Equity On Customer's Retention Top White Coffee In Bandar Lampung - Susi Indriyani (Prosiding International conference on Information Technology and Business (ICITB), 2017)
The purpose of this research is to know the effect of brand equity on top white coffee customerretention in Bandar Lampung. Analyzer that is used in this research is validity and reliability test, classical assumption test included normality test, heteroskedasticity test, and multicollinearity test. A statistical tool that is used is multiple linear regression analysis and hypothesis test consisting of test coefficient of determination (R²), F test and t-test. The dependent variable in this research is customer retention. While the independent variables in this research are brand awareness, quality perception, brand association and brand loyalty. The type of research is descriptive. The population in this research is the people of Bandar Lampung city by the taking sampling technique using incidental sampling technique with the number of samples as much as 161 people. The results of research show that simultaneously brand awareness, quality perception, brand association and brand loyalty together significantly influence customer retention. On the other hand, partially brand awareness and quality perception do not have a significant effect on customer retention. Meanwhile, brand associations and brand loyalty have a significant effect on customer retention.Keywords: Brand Equity, and Customer Retention.